Using information technology to support knowledge conversion processes (Information Research: An International Electronic Journal)
One of the main roles of Information Technology in Knowledge Management programs is to accelerate the speed of knowledge transfer and creation. The Knowledge Management tools intend to help the processes of collecting and organizing the knowledge of groups of individuals in order to make this knowledge available in a shared base. Due to the largeness of the concept of knowledge, the software market for Knowledge Management seems to be quite confusing. Technology vendors are developing different implementations of the Knowledge Management concepts in their software products. Because of the variety and quantity of Knowledge Management tools available on the market, a typology may be a valuable aid to organizations that are looking for answers to specific needs. The objective of this article is to present guidelines that help to design such a typology. Knowledge Management solutions such as intranet systems, Electronic Document Management (EDM), groupware, workflow, artificial intelligence-based systems, Business Intelligence (BI), knowledge map systems, innovation support, competitive intelligence tools and knowledge portals are discussed in terms of their potential contributions to the processes of creating, registering and sharing knowledge. A number of Knowledge Management tools (Lotus Notes, Microsoft Exchange, Business Objects, Aris Toolset, File Net, Gingo, Vigipro, Sopheon) have been checked. The potential of each category of solutions to support the transfer of tacit and/or explicit knowledge and to facilitate the knowledge conversion spiral in the sense of Nonaka and Takeuchi (1995) is discussed.